2004
DOI: 10.1523/jneurosci.1990-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Differential Cortical Input to Direct Pathway versus Indirect Pathway Striatal Projection Neurons in Rats

Abstract: The two main types of corticostriatal neurons are those that project only intratelencephalically (IT-type), the intrastriatal terminals of which are 0.41 m in mean diameter, and those that send their main axon into pyramidal tract and have a collateral projection to striatum (PT-type), the intrastriatal terminals of which are 0.82 m in mean diameter. We used three approaches to examine whether the two striatal projection neuron types (striatonigral direct pathway vs striatopallidal indirect pathway) differ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
258
6
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(293 citation statements)
references
References 64 publications
(134 reference statements)
28
258
6
1
Order By: Relevance
“…It is possible, however, that there is heterogeneity when considering subdivisions of the corticostriatal or thalamostriatal pathways. Indeed, previous anterograde labeling studies have indicated that subpopulations of cortical afferents show selectivity for direct or indirect pathway MSNs (Hersch et al, 1995;Lei et al, 2004), and afferents from the CM nucleus of the squirrel monkey selectively innervate neurons of the direct pathway (Sidibé and Smith, 1996). Furthermore, microstimulation of sensorimotor cortex and local disinhibition of primary motor cortex both result in upregulation of early-gene expression primarily within indirect pathway neurons (Berretta et al, 1997;Parthasarathy and Graybiel, 1997).…”
Section: Cortical and Thalamic Input To Direct And Indirect Pathway Msnsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, however, that there is heterogeneity when considering subdivisions of the corticostriatal or thalamostriatal pathways. Indeed, previous anterograde labeling studies have indicated that subpopulations of cortical afferents show selectivity for direct or indirect pathway MSNs (Hersch et al, 1995;Lei et al, 2004), and afferents from the CM nucleus of the squirrel monkey selectively innervate neurons of the direct pathway (Sidibé and Smith, 1996). Furthermore, microstimulation of sensorimotor cortex and local disinhibition of primary motor cortex both result in upregulation of early-gene expression primarily within indirect pathway neurons (Berretta et al, 1997;Parthasarathy and Graybiel, 1997).…”
Section: Cortical and Thalamic Input To Direct And Indirect Pathway Msnsmentioning
confidence: 99%
“…Given that the excitatory inputs to the striatum from the cortex and thalamus are fundamental in the expression of basal ganglia function, it is critical to elucidate the pattern of innervation of the two subpopulations of MSNs. Both direct and indirect pathway MSNs have been shown to receive synaptic input from the cortex (Somogyi et al, 1981;Hersch et al, 1995;Lei et al, 2004). Light microscopic studies have suggested that the same is true for thalamostriatal afferents (Lanciego et al, 2004;Castle et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One group exclusively projects to the external pallidal segment (GPe-exclusive cells; indirect pathway), whereas another group, while sending axon collaterals to the external pallidal segment, directly projects to output structures in the basal ganglia (direct pathway cells) (Kawaguchi et al, 1990;Lévesque and Parent, 2005). Direct pathway cells are considered to promote desired movements, and GPe-exclusive cells are considered to inhibit unwanted movement (Albin et al, 1989;DeLong, 1990;Lei et al, 2004). Recently, it has been revealed that two types of corticostriatal cells differentially innervate one of the above two striatal output cells (Reiner et al, 2003;Lei et al, 2004).…”
Section: Functional Differentiation Of Corticostriatal Pathwaysmentioning
confidence: 99%
“…Because different classes of corticostriatal cells innervate distinct populations of striatal cells (Lei et al, 2004) that have opposing effects on the outputs of basal ganglia (Albin et al, 1989;Alexander and Crutcher, 1990), knowledge of the patterns of synaptic connectivity between corticostriatal cells may suggest a physiological substrate for cortical influence on the basal ganglia circuitry. To this end, we investigated the synaptic connections between retrograde-labeled CCS and CPn pyramidal cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no evidence, to our knowledge, that the crossed connection preferentially carries the information of the D 1 receptor (i.e., direct) pathway. On the input side, there is a hint for the difference in laterality: caudate neurons in the direct and indirect pathways tend to receive bilateral and ipsilateral cortical projection, respectively (Lei et al, 2004). It is possible that the outputs of these caudate neurons are organized in the same manner.…”
Section: Dopamine D 2 -Mediated Effects On Reward-modulation Of Saccadesmentioning
confidence: 99%